Pollens of 120 plant taxa in Nui Chua national park, Ninh Thuan province - Lam, Trinh Thi (Academia Journal of Biology, 2012)
The pollen morphology of 120 species from Nui Chua national park, Ninh Thuan province belonging to 47 families of dicotyledons, angiosperms were examined using light microscope. Pollen samples were acetolysed following the technique of Erdtman [3]. Pollen grains are usually categorized largely on the basis of their shape, size, apertural types, symmetry, polarity and exine sculpturing. However, from a phylogenetic and evolution point of view, polarity, symmetry, apertural types and exine sculpturing are the most important characters. Dicotyledons are generally characterized by radially symmetrical, isopolar, colporate, colpate and porate pollen [6]. The pollen grains examined were usually monads, but tetrads and polyads were also found in Annonaceae, Mimosaceae and Asclepiadaceae. Pollen grains were radially symmetrical, isopolar - rarely apolar and subisopolar. They were generally prolate - spheroidal to oblate - spheroidal or subprolate to prolate, rarely sphaeroidal. In apertural types mostly colporate, colpate and porate, rarely non - aperturate grains were observed. Aperture differed in number, position and structure. From pollen grains examined, tricolporate grains were fairly common. According to Doyle [1] and Muller [5], they are in fact numerically dominant in the modern dicot flora. In some families as Lythraceae, Melastomataceae, more distinct heterocolpate grains were also found. Similarly, exine sculpturing was also varied, ranging from almost reticulate, psilate, granulate, striate, scabrate and echinate. Almost families were fairly uniform in their exine pattern. In contrast to this, some families viz. Anacardiaceae, Sterculiaceae showed great diversity in their exine pattern.